Differentiate between the concepts of Displacement and Asylum - صفطلي , مايا; غانم, فلك (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The Concepts Of Asylum and Displacement have been linked the population movement, Man has known movement from one place to another since ancient times. Despite the ambiguity of the two definitions, they shouldn’t be confused, as the difference is important, The meeting point of Internal Displaced Persons and Refugees lies in their union in terms of reason, meaning that both leave their place of residence and move to another place in search of safety, either because of tensions, conflicts or persecution, but they differ in the spatial aspect "arrival point", which means that the refugee enjoys a legal system other than the one that proves to the internally displaced persons that the refugee changes his legal status in the country of asylum in order the country's borders, which is the separation point between the displaced person who didn’t cross the borders of his country and the refugee who left it, Often, the country to which asylum is sought provides a safe place, food, shelter and protection for the refugee in accordance with international laws and treaties, and the United Nations High Commissioner for refugees is concerned with refugees affairs and helps them start their lives again, unlike a displaced whose fate remains completely suspended under the control of his local government, In addition to the absence of international conventions addressing the issue of internal displacement.